2013
DOI: 10.1002/ccd.24863
|View full text |Cite
|
Sign up to set email alerts
|

Effects of percutaneous revascularization of chronic total occlusions on clinical outcomes: A meta‐analysis comparing successful versus failed percutaneous intervention for chronic total occlusion

Abstract: As compared to conservative management (as a result of failed intervention), successful PCI recanalization of a CTO appears to be associated with improved long-term clinical outcomes; however, randomized controlled trials (RCTs) are needed to further confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(60 citation statements)
references
References 49 publications
0
55
0
5
Order By: Relevance
“…Finally, increasingly more studies provide data on the role of CTO as an predictor of sudden cardiac death, and long-term mortality [18]. In a recent meta-analysis of 23 observational studies, Khan et al [19]. found that successful recanalization of a CTO resulted in improved all-cause mortality, and lower rates of major adverse cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, increasingly more studies provide data on the role of CTO as an predictor of sudden cardiac death, and long-term mortality [18]. In a recent meta-analysis of 23 observational studies, Khan et al [19]. found that successful recanalization of a CTO resulted in improved all-cause mortality, and lower rates of major adverse cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…21 Moreover, previous studies focused on the association of successful CTO revascularization with clinical outcome compared with failed PCI among patients who underwent PCI. 2-5, 22 Therefore, we investigated the clini- …”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…22 To date, most observational studies in which successful CTO recanalization was compared with failed CTO-PCI in a head-to-head fashion did not include patients managed medically without a CTO-PCI attempt. Accordingly, the strengths of our study may reflect the purely clinical significance of PCI as a planned treatment strategy by comparison with medical management alone for the treatment of CTO.…”
Section: Disclosures/grant Supportmentioning
confidence: 99%
“…In non-randomized trials, successful recanalization of these CTOs has shown to improve survival, cardiac function and overall quality of life [2,[4][5][6][7]. Nevertheless, 40% of these patients are treated medically or a large portion of these patients is referred for coronary artery bypass grafting (CABG) surgery, especially those with multivessel disease and a high syntax-score [3].…”
Section: Introductionmentioning
confidence: 99%